WORKING CAPITAL MANAGEMENT AND PROFITABILITY OF QUOTED COMPANIES IN NIGERIA AND SOUTH AFRICA - Masud, Abdullahi; Aliyu, Usman Baba; Yusuf, Abdullahi Babandako; Ndagi, Salihu; Yusuf, Mohammed Abdullahi; Shu’uibu, Bawa A. (Kashere Journal of Management Sciences, 2024)
The study examines the relationship between working capital management and firm’s profitability. In this research study, involving Nigeria firms and South Africa firms for effective and efficient comparison. This gives an essential source of information to have a large sample size in the study. However, the previous literature which discovered that there is a severe lacks of literature on WCM and firm’s profitability especially in Nigeria and South Africa. The underlying components that influence the profitability have not been comprehensively explored in Nigeria and South Africa. Therefore, the main objective is to examine the effect of WCM and its components on firm’s profitability. The study uses 187 samples and panel data of 935 firm year observations derived from the quoted companies on the Nigeria Stock Exchange and Johannesburg Stock Exchange from 2018 to 2022. The data obtained were analysed by means of multiple regression analyses encompassing correlation and panel data regression analyses. Study is underpinned by Agency theory. This study found that the association between WCM variables on firm’s profitability have maximum level of investment on how WCM can produce favourable returns to the shareholders of the company. Finally, the study has implications for captains of industries to devise the most effective and efficient means of managing companies in both Nigeria and South Africa.